Antibodies Elicited by the Shigella sonnei GMMA Vaccine in Adults Trigger Complement-Mediated Serum Bactericidal Activity: Results From a Phase 1 Dose Escalation Trial Followed by a Booster Extension - Micoli, Francesca; Rossi, Omar; Conti, Valentino; Launay, Odile; Sciré, Antonella Silvia; Aruta, Maria Grazia; Nakakana, Usman Nasir; Marchetti, Elisa; Rappuoli, Rino; Saul, Allan; Martin, Laura B.; Necchi, Francesca; et al. (Frontiers in Immunology, 2021)
Shigella is the second most deadly diarrheal disease, after rotavirus, with high morbidity and mortality in developing countries. Currently, no vaccine is widely available, and the increasing levels of multidrug resistance make Shigella a high priority for vaccine development. GSK Vaccines Institute for Global Health (GVGH) has developed a single component candidate vaccine against Shigella sonnei (1790GAHB) using the GMMA technology, with the O antigen (OAg) portion of lipopolysaccharide (LPS) as active moiety. The vaccine was well tolerated and induced high anti-S. sonnei LPS serum immunoglobulin G (IgG) antibody levels in early-phase clinical trials. In a phase 1 placebo-controlled dose escalation trial in France (NCT02017899), three doses of five different vaccine formulations (0.06/1, 0.3/5, 1.5/25, 3/50, 6/100 µg of OAg/protein) were administered to healthy adults. In the phase 1 extension trial (NCT03089879) conducted approximately 3 years following the parent study, primed individuals received a booster 1790GAHB dose (1.5/25 µg formulation). Controls were vaccine-naïve participants immunized with one vaccine dose. The current analysis assessed the functionality of sera collected from both studies using a high-throughput luminescence-based serum bactericidal activity (L-SBA) method developed at GVGH and optimized for testing human sera. Antibodies with complement-mediated bactericidal activity were detected in vaccinees but not in placebo recipients. SBA titers increased with OAg dose, with a persistent response for more than 2 years after the first primary vaccination schedule containing at least 1.5/25 µg of OAg/protein. The booster dose induced a strong increase of SBA titers in most primed participants. Correlation between SBA titers and anti-S. sonnei LPS serum IgG was also verified. These results suggest that GMMA is a promising OAg delivery system for the generation of functional antibody responses and persistent immunological memory.